A regional programme to collect plasma for preparation of human immunoglobulin anti-rabies. Issue 2 (February 1980) - Crawford, R J; Morgan, M; Mitchell, R
Abstract : We identified over 100 recipients of rabies vaccine (human diploid cell vaccine) and recruited them as plasma donors. Some were plasmapheresed at static centres, others by mobile teams. The operation of these teams is described in detail. No plasma was sent to the Fractionation Centre until the date of vaccination had been checked. Assay results showed that the majority of plasma collected between four and 20 weeks after the second dose of vaccine contained 6 or more IU/ml.